Polyurethane films seeded with embryonic stem cell-derived cardiomyocytes for use in cardiac tissue engineering applications - Alperina, C.; Zandstrab, P.W.; Woodhouse, K.A.
Cardiomyocytes are terminally differentiated cells and therefore unable to regenerate heart tissue after infarction. The successful engraftment of various cell types resulting in improved cardiac function has been reported,however methods for improving the delivery of donor cells to the infarct site still need to be developed. The use of bioengineered cardiac grafts has been suggested to replace infarcted myocardium and enhance cardiac function. In this study,we cultured embryonic stem (ES)cell-derived cardiomyocytes on thin polyurethane (PU)films. The films were coated with gelatin,laminin or collagen IV in order to encourage cell adhesion. Constructs were examined for 30 days after seeding. Cells cultured on laminin and collagen IV,exhibited preferential attachment,as assessed by cellular counts,and viability assays. These surfaces also resulted in a greater number of contracting films compared to controls. A degradable elastomer seeded with embryonic stem cell-derived cardiomyocytes may hold potential for the repair of damaged heart tissue
Keywords: EMBRYONIC STEM CELLS; CARDIOMYOCYTES; BIODEGRADABLE POLYURETHANE; ECM; CARDIAC TISSUE ENGINEERING